Makrofauna Tanah Sebagai Bioindikator pada Areal Perkebunan yang diberi Limbah Cair Pabrik Kelapa Sawit Sebagai Pupuk - Arlen Hanel John (Dinamika Lingkungan Indonesia, 2022)
Research on Soil Macrofauna as Bioindicator in Plantation Areas Given Palm Oil Mill Liquid Waste as Fertilizer was conducted in 2021. Samples were taken in Long Bed, Flat Bed, and Control areas using Purposive Sampling and Squares and Hand Sorting methods. Each location is determined by 9 sampling points. Soil macrofauna samples were identified in the USU FMIPA Ecology laboratory. From the results of the study, there were 3 soil macrofauna phyla, namely the Annelida phylum, which consisted of 1 class, 1 order, 2 families, and 2 species. Phylum Arthropoda consists of 5 classes, 10 orders, 16 families, and 27 species. Phylum Mollusca consists of 1 class, 1 order, 1 family, and 1 species. The highest population density (K) was obtained from the species Macrotermes gilvus, which was 81.10 individuals/m2 in the Control area, followed by Ponthoscolex corethrurus at 78.81 individuals/m2 in the Flat Bed area. The highest relative density (KR) was found in the species Macrotermes gilvus, which was 49.1% in the control area, followed by Ponthoscolex corethrurus at 46.84% in the Long Bed area. The highest frequency of presence (FK) was found in the Ponthoscolex corethrurus species, which was 100% in the Control and Flat Bed areas, and 88.88% in the Long Bed areas. Species that can live and reproduce well as bioindicators are Ponthoscolex corethrurus in the Long Bed area, followed by the Flat Bed and Control areas. The highest diversity index value was found in the Flat Bed area, which was 3,831 with the criteria for diversity being high, the distribution of the number of individuals for each species was high, the community stability was good and the soil community had not been polluted, while the Equitabilitas value was 1,258 with the criteria for high uniformity, stable community. The application of palm oil mill effluent as fertilizer to the plantation area can increase the life of the soil macrofauna, and the physical-chemical properties of the soil.